Policy Rationales for Early Childhood Services - Penn, Helen (International journal of child care and education policy (Seoul), 2011)
This article explores the rationales and the research paradigms that countries have used to underpin policies on early childhood education and care (ECEC) services and to justify expenditure on them. Globalization — here narrowly defined as the global spread of theories and practices about early childhood mainly emanating from Euro-American sources — has led to some convergence of rationales, especially economic rationales. But within countries rationales almost always have deep historical roots, and reflect cultural ideas of motherhood, family, childhood, work and the role of the state. Perspectives may be incompatible yet sit alongside one another without the contradictions being addressed. Policy development and implementation are rarely straightforward or coherent, particularly when early education and care spans several policy areas. The article summarizes the differences between rationales and indicates in which country or groups of countries they are most likely to be found.